2011
DOI: 10.3758/s13414-011-0220-9
|View full text |Cite
|
Sign up to set email alerts
|

Letter processing and font information during reading: Beyond distinctiveness, where vision meets design

Abstract: Letter identification is a critical front end of the reading process. In general, conceptualizations of the identification process have emphasized arbitrary sets of distinctive features. However, a richer view of letter processing incorporates principles from the field of type design, including an emphasis on uniformities across letters within a font. The importance of uniformities is supported by a small body of research indicating that consistency of font increases letter identification efficiency. We review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 75 publications
(189 reference statements)
0
28
0
Order By: Relevance
“…Indeed, it would be rather surprising if the default settings (not based on empirical data) were optimal. The vast majority of experiments with developing readers has focused on the impact of sublexical/lexical factors in visual-word recognition and reading (e.g., length, neighbourhood size, orthographic consistency, regularity, word-frequency age-ofacquisition, etc; see Defior, Jimenez-Fernandez, & Serrano, 2009;Manolitsis, Georgiou, & Parrila, 2011;Manolitsis, Georgiou, Stephenson, & Parrila, 2009;Verhoeven, Schreuder, & Baayen, 2006;Wang, Castles, Nickels, & Nation, 2011), whereas e as occurs with adult skilled readers e much less attention has been paid to the influence of perceptual factors such as font, letter size, or inter-letter spacing (see Tinker, 1963, for early research on typographical factors during reading; see also Sanocki & Dyson, 2012, for a recent review). The present study represents a modest effort to shed some light on role of a potentially important parameter such as inter-letter spacing during visual-word recognition and reading with developing readers.…”
Section: Introductionmentioning
confidence: 98%
“…Indeed, it would be rather surprising if the default settings (not based on empirical data) were optimal. The vast majority of experiments with developing readers has focused on the impact of sublexical/lexical factors in visual-word recognition and reading (e.g., length, neighbourhood size, orthographic consistency, regularity, word-frequency age-ofacquisition, etc; see Defior, Jimenez-Fernandez, & Serrano, 2009;Manolitsis, Georgiou, & Parrila, 2011;Manolitsis, Georgiou, Stephenson, & Parrila, 2009;Verhoeven, Schreuder, & Baayen, 2006;Wang, Castles, Nickels, & Nation, 2011), whereas e as occurs with adult skilled readers e much less attention has been paid to the influence of perceptual factors such as font, letter size, or inter-letter spacing (see Tinker, 1963, for early research on typographical factors during reading; see also Sanocki & Dyson, 2012, for a recent review). The present study represents a modest effort to shed some light on role of a potentially important parameter such as inter-letter spacing during visual-word recognition and reading with developing readers.…”
Section: Introductionmentioning
confidence: 98%
“…Further, substantial research by Sanocki and his colleagues has shown that letter recognition relies on defining a set of features whose membership relies on distinctiveness as well as commonalities (e.g. [61]). In addition, commonalities may be important for defining a category of letter, while distinctiveness may help to process sub-ordinate categories, such as type-face or font [61].…”
Section: Introductionmentioning
confidence: 99%
“…[61]). In addition, commonalities may be important for defining a category of letter, while distinctiveness may help to process sub-ordinate categories, such as type-face or font [61]. …”
Section: Introductionmentioning
confidence: 99%
“…Studies focusing on the issues surrounding screen reading, as it differs from reading on paper, have typically considered typeface as a secondary factor (Gould, Alfaro, Barnes, et al 1987; Gould, Alfaro, Finn, et al 1987; Sheedy et al 2005, 2008; Slattery and Rayner 2009), often in combination with examinations of font smoothing (anti-aliasing) algorithms (Gugerty et al 2004; Sheedy et al 2005, 2008). These studies often examine typefaces with obvious stylistic differences, such as between serif and sans-serif type or blackletter families (Rayner et al 2006; Moret-Tatay and Perea 2011; Perea, Moret-Tatay, and Gómez 2011; Sanocki and Dyson 2011), but comparisons of typefaces within the same stylistic family are relatively rare (though Gould et al’s early work does examine this, albeit as a secondary focus, as previously noted). Moreover, such studies have often utilised reading comprehension metrics to gauge legibility, and importantly, usually present participants with traditional long-form reading tasks.…”
Section: Introductionmentioning
confidence: 99%